Synthesis and Biological Evaluation of Novel Imidazotetrazines - Summers, Helen S (2019)
Glioblastoma Multiforme (GBM) is the most prevalent form of primary brain tumour in adults and is very fast growing. Current treatment involves surgery, radiotherapy and chemotherapy with the alkylating agent temozolomide (TMZ; 1), however innate and acquired resistance often develop after initial TMZ treatment. To overcome both forms of TMZ resistance, N-3 propargyl, C-8 thiazole-containing analogues were synthesised. Activity of these compounds improved up to 14.5-fold in TMZ-sensitive cell line U373V (GBM) and 73.8- and 54.4-fold in TMZ-resistant cell lines U373M (GBM) and HCT-116 (colorectal carcinoma; CRC) respectively compared to TMZ. Smaller thiazole substituents resulted in increased activity; thiazole-containing analogues 2, 3 and 4 were chosen for further studies. These compounds showed excellent broad-spectrum activity across a range of cancer cell lines, and 3 expressed a selectivity index of 7.6, comparable to 7.8 of TMZ, when tested in MRC-5 fibroblasts. 1H NMR decomposition studies showed analogues undergo similar decomposition as TMZ. Drug metabolism and pharmacokinetic (DMPK) studies (chemical and metabolic stability, permeability) identified 3 as a lead compound with the desired chemical stability profile for an orally available drug. It also showed good permeability, far improved over TMZ, suggesting an alternative drug candidate for GBM treatment.